PENGGUNAAN HAK INISIATIF ANGGOTA DPRD SUKOHARJO DALAM PEMBENTUKAN PERATURAN DAERAH DITINJAU DARI UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Sadewa, Gandhi Mas Dias; Maharani, Andina Elok Puri (Res Publica: Jurnal Hukum Kebijakan Publik, 2019)
Gandhi Mas Dias Sadewa, E0014172, Implementation Of The Rights Of Initiative Of The Members Of The Sukoharjo Regional Parliament For The Establishment Of Regional Regulations Judging By The Law Number 23 Of 2014 concerning The Regional GovernmentThis study aims to find out how the implementation of the rights of initiative byDPRD of Sukoharjo Regency and the obstacles encountered and the implementation of the rights of initiative and the formation of regional regulations. The kind of research used in this research is a normative-empirical and descriptive legal research.The type of used data is primary data and secondary data. The source of primary data is direct interview  with related parties of the research. The sources of secondary data are literature, regulations, journals, articles and materials from the internet and other related sources.Technique of data collection that be used are field studies which directed to the object of research and literature study to obtain theoretical basis related to the research.Based the result of the research and discussion The implementation and use the rights of the DPRD initiative of Sukoharjo Regency and the implementation of the regional regulations of the initiative were carried out in accordance with the standards in force but their use has not been maximized. By exercising its right of initiative for the formation of the local supplementation of the initiative, the DPRD of the Sukoharjo regency encountered various obstacles.